(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2013)
Throughout this paper those technical and accounting concepts of the Law of mining privileges that generate ambiguity and incongruity for businesses has been analyzed and identified. For this reason, we have developed a proposal amending the calculation of mining privileges based on two main aspects: (i) terminology used in the law and (ii) establishment of income before retribution to stakholders and taxes as a basis for calculating privileges. As a result, it was established as an object of study for all mining companies paying privileges; however, for purposes of the investigation three representative mining companies of medium and large mining were selected. Later interviews were arranged with financial and tax managers of the companies mentioned above as well as experts in the field of mining privileges; it was concluded that the concepts of "cost" and "corresponding fiscal year" mentioned in the Law generated ambiguities, inconsistencies and accounting distortions. Also, mining companies and experts agreed that the current basis for the calculation of the privileges is not adequate for the mining sector since it does not reflect the financial situation of companies. Therefore, a proposal for reformulation of the applied priviously and a new basis for calculating the mining privileges based on the cost of sales is made; since, in the cost of sales is found what Kieso and Weygandt (1999) denominated as "the price paid for the right to seek and find a hidden Natural resources, or paid by a source already discovered"